Pengaruh Green Marketing Dan Consumer Behaviour Terhadap Pembentukan Brand Image Pada Produk Kosmetik (Studi Kasus The Body Shop Kota Kasablanka Jakarta Selatan) - Aliza Faila Sufa; Hartono Hartono; Anita Maulina (JAMBIS : Jurnal Administrasi Bisnis, 2021)
The main purpose of this research is to know the impact of green marketing and consumer behavior on consumer brand image of cosmetic products for The Body Shop Casablanca city, South Jakarta. In this research, the author used a descriptive method with a quantitative approach and 100 participate consumers who used a cosmetic product of Body Shop and know that are green products. The sampling technique in this study used nonprobability sampling with the purposive sampling method. Data were collected through questionary. The analyzed method in this research is multiple linear regression test with SPSS IBM Statistic Version 24 application. The results of this study show that the green marketing variable has a significant influent on customer behavior about 31,2%. For that consumer behavior, a variable has a significant influent to brand image about 30,8%. The effect of green marketing and consumer behavior variables simultaneously have a significant impact to brand image about 34,3%.  Then from the test of this research green marketing variables quite strong for attracting consumer behavior for brand image cosmetic product The Body Shop can thrive as well. Keywords: Green Marketing; Consumer Behaviour; Brand Image